Clinical and epidemiological profile of patients presenting with inflammatory myelopathies - Panthee, Pradeep; Gajurel , Bikram Prasad; Karn, Ragesh; Rajbhandari, Reema; Ojha, Rajeev; Ghimire, Pukar; Sahi , Sumit; Bhandari , Pragya; Lamichhane, Jayram; Thapa, Sujan; Kayastha, Suresh; Paudel, Jibika; et al. (Nepal Mediciti Medical Journal, 2025)
BACKGROUND Inflammatory myelopathies, a group of disorders characterized by spinal cord inflammation, include conditions such as transverse myelitis (TM), neuromyelitis optica spectrum disorder (NMOSD), and multiple sclerosis (MS)-related myelitis. These disorders, driven by autoimmune, infectious, or post-infectious etiologies, present significant neurological challenges globally. Despite their impact, epidemiological data, particularly from resource-limited settings like Nepal, remain scarce, hindering effective diagnosis and management. This retrospective study aims to address this knowledge gap by examining the epidemiological, clinical, and outcome profiles of inflammatory myelopathies at a tertiary care center in Nepal. METHODS This single-center, retrospective cohort study was conducted at the Department of Neurology, Tribhuvan University Teaching Hospital (TUTH), Kathmandu, Nepal, from April 14, 2023, to November 16, 2024. It included 56 patients with confirmed inflammatory myelopathies, diagnosed based on clinical and radiological findings. Data were extracted from electronic medical records using a structured proforma, covering demographics, clinical features, treatment modalities, and functional outcomes assessed at presentation and three months post-discharge. RESULTS The study cohort had a mean age of 38.53 ± 15.96 years, with a female predominance (58.90%). NMOSD was the most common diagnosis (39.30%), followed by myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) and infectious/para-infectious myelitis (16.10% each). Longitudinally extensive transverse myelitis (LETM) was observed in 64.30% of cases, with 76.80% showing cranial symptoms and 62.50% experiencing bladder involvement, 97% of which persisted at follow-up. Intravenous methylprednisolone was the primary acute treatment (96.40%), while 39.30% received rituximab for long-term immunosuppression. Functional independence improved from 42.85% at presentation to 75.5% at follow-up, indicating a positive treatment response. CONCLUSIONS This study provides the first comprehensive insight into inflammatory myelopathies in Nepal, highlighting a high prevalence of NMOSD and significant morbidity from persistent bladder symptoms. The findings underscore the efficacy of early immunotherapy, despite resource constraints limiting access to advanced treatments like plasma exchange.